Answer:
The first three terms are -30, -27 and -24
Explanation:
The formula for nth term of a arithmetic series is given by:
aₙ = a₁ + (n - 1)d
Substitute n = 16 in the given equation:
a₁₆ = a₁ + (16 - 1)d
Where aₙ = a₁₆ = 15. Substitute in the given equation
15 = a₁ + 15d ⇒ Equation (i)
Sum of arithmetic sequence is given by:
Sₙ = n(a₁ + aₙ) / 2
Substitute n = 16 in the above equation:
S₁₆ = 16(a₁ + a₁₆) / 2
Where S₁₆= -120 and a₁₆=15, substitute:
-120 = 16(a₁ + 15)/2
-240 = 16(a₁ +15)
-15 = a₁ + 15
a₁ = -30
Substitute it in Equation (i)
15 = a₁ + 15d
15 = -30 + 15d
15d = 15+30
d = 45/15
d = 3
So
a₁ = -30
a₂ = a₁ + (2-1)d
a₂ = -30 + 3
a₂ = -27
a₃ = a₁ + (3-1)d
a₃ = a₁ + 2d
a₃ = -30 + 2(3)
a₃ = -30 +6
a₃ = -24